Pengaruh Pemberian Susu Kedelai (Glycine Max) Terhadap Peningkatan Produksi ASI Pada Ibu Post Partum - Devina Devina; Utari Christya Wardhani; Elvi Murniasih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Unsmooth milk production is the main problem causing the failure of the breastfeeding process. One way to increase milk production for post partum mothers is to support the nutritional needs of mothers, one of which is by consuming soy milk made from soy beans. This study aims to determine the effec tof soymilk (Glycine Max) on breast milk production in post partum mothers at Bakti Timah Hospital Karimun Riau Archipelgo. This researchis a pre-experimental study with a one-group pretest-posttest design. The population in this study were post partum mothers at Bakti Timah Hospital Karimun Riau Archipelago in the last one month as many as 102 people. The sampling technique in this study used a sampling technique carried out using purposive sampling of 34 respondents. The research instrument used a breastmilk production questionnaire, namely the Lactation Assessment Tool (LATCH) which consisted of 5 points. Data analysis was performed univariately and bivariately using the Wilcoxon test. The results showed that before consuming soy milk the average milk production was 3.35 and after being given soy milk the average milk production increased to 4.03. The results of the Wilcoxon test found a p-value of 0.001 (p <0.05) so it can be concluded that there is an effect of soy milk (Glycine Max) on increasing milk production in post partum mothers. It is recommended for the community, especially post partum mothers, to be able to use soy milk as an alternative to addressing problems with increasing breast milk production.